Leading in the digital age: The role of leadership in organizational digital transformation - Sacavém, A. (2025)
In the modern digital age, organizations face unprecedented challenges and possibilities while managing the intricacies of digital transformation. Accelerated technological developments, changing customer preferences, heightened competition, and dynamic regulatory environments necessitate companies to synchronize their business goals with technological innovations. Leadership is crucial in steering businesses through changes, requiring a deep understanding of change processes and the capacity to adjust leadership accordingly. This research addresses the central question: How does leadership effectively promote organizational digital transformation? The study examines how leaders can effectively promote the adoption of advanced technologies and the promotion of innovation, by first exploring the nature of digital transformation within organizations and then analyzing the evolving dynamics of leadership in this context. An integrative review of the Web of Science (WoS) and Scopus databases was conducted, using the search terms: “Leadership” and “Digital Transformation”. The findings emphasize that effective leadership is crucial for managing the minutiae of digital transformation, integrating technology into organizational processes to facilitate learning, collaboration, and agility, enabling companies to adapt to market shifts, reduce uncertainty, and enhance decision-making for sustainable growth. By using the right tools and with the right frequency, leaders may develop team cohesion—even at a distance. Attentive digital-age leaders will know how to leverage the right mechanisms, and herein, we hope to give some indication of how that may be achieved, so that digital transformation increases rather than decreases team motivation levels.